Evaluasi Kinerja Long Belt Jalur 71 Untuk Pengangkutan Limestone di PT. Semen Padang Kecamatan Lubuk Kilangan Provinsi Sumatera Barat. - Jeffrey Leonardi Nurkamal; Mulya Gusman (Departemen Teknik Pertambangan FT UNP, 2022)
. PT Semen Padang is one of the departments in the oldest cement company in Southeast Asia, namely PT Semen Padang. The mining department is tasked with supplying the company's basic needs, namely limestone or limestone as raw material for cement production. The mining department of PT Semen Padang is located about 10 km to the east of the factory site so that in delivering limestone material PT Semen Padang uses a belt conveyor as the material conveying medium.The evaluation carried out on the belt conveyor which has a small capacity is carried out by changing the gear box specifications to a higher specification in accordance with the maximum capability of the belt so that it is expected that the speed of the conveyor belt will increase and increase the capacity of the conveyor belt so that production and material delivery can be maximized and can meet the company's limestone production target of 26,181 tons/day, in December there were several days that did not meet the production target and the lowest was only 4,500 tons/day. Recommendations to increase the productivity of the 6A1J03 belt conveyor with a speed of 1.5 m/s, an angle of 20° and a belt width of 3000 mm with a yield of 2939,632 tons/hour and for a 6A1J10 belt conveyor with a speed of 2.5 m/s, an angle of 35° and belt width 1600 mm with a yield of 2587.02 tons/hour.